Live-attenuated lymphocytic choriomeningitis virus-based vaccines for active immunotherapy of HPV16-positive cancer. (1st January 2020) - Schmidt, Sarah; Bonilla, Weldy V.; Reiter, Andrea; Stemeseder, Felix; Kleissner, Theresa; Oeler, Daniel; Berka, Ursula; El-Gazzar, Ahmed; Kiefmann, Bettina; Schulha, Sophie C.; Raguz, Josipa; Habbeddine, Mohamed; et al.
ABSTRACT: Infection with human papillomavirus (HPV) is associated with a variety of cancer types and limited therapy options. Therapeutic cancer vaccines targeting the HPV16 oncoproteins E6 and E7 have recently been extensively explored as a promising immunotherapy approach to drive durable antitumor T cell immunity and induce effective tumor control. With the goal to achieve potent and lasting antitumor T cell responses, we generated a novel lymphocytic choriomeningitis virus (LCMV)-based vaccine, TT1-E7E6, targeting HPV16 E6 and E7. This replication-competent vector was stably attenuated using a three-segmented viral genome packaging strategy. Compared to wild-type LCMV, TT1-E7E6 demonstrated significantly reduced viremia and CNS immunopathology. Intravenous vaccination of mice with TT1-E7E6 induced robust expansion of HPV16-specific CD8 + T cells producing IFN-γ, TNF-α and IL-2. In the HPV16 E6 and E7-expressing TC-1 tumor model, mice immunized with TT1-E7E6 showed significantly delayed tumor growth or complete tumor clearance accompanied with prolonged survival. Tumor control by TT1-E7E6 was also achieved in established large-sized tumors in this model. Furthermore, a combination of TT1-E7E6 with anti-PD-1 therapy led to enhanced antitumor efficacy with complete tumor regression in the majority of tumor-bearing mice that were resistant to anti-PD-1 treatment alone. TT1-E7E6 vector itself did not exhibit oncolytic properties in TC-1 cells, while the antitumor effect was associated with the accumulation of HPV16-specific CD8 + T cells with reduced PD-1 expression in the tumor tissues. Together, our results suggest that TT1-E7E6 is a promising therapeutic vaccine for HPV-positive cancers.